(untitled) (Prostor, 2022)
As a state architect in the Kingdom of Serbs, Croats and Slovenes (since 1929 the Kingdom of Yugoslavia), who built about ninety buildings of various purposes on the territory, Momir Korunović (1883-1969) has left a tangible creative mark in Croatia. Besides one built and one unstructured Orthodox Church in continental Croatia, he designed four public buildings on the Adriatic coast, in the areas that belonged to the Savska and Primorska Banovina, out of which two were realized. Modestly adjusted to the architectural tradition and climate, his works in the Adriatic area did not differ significantly from the work he completed in other parts of the multinational state. Anti-modern and conservative, they contain elements of the Yugoslav unitary style (projects of the Main Post Office in Split and Student Dormitory in Šibenik), and the national style of the Orthodox churches on Vis and Sušak. For a more significant architectural result on the Croatian Adriatic coast, Korunović obviously needed to go one step further and more fully adapt to local conditions and cultural tradition. However, he was not ready for that, because in his creative consciousness he fixed a conservative matrix of neo-medieval style in the early twenties and enriched with deposits of post-secession and expressionism, which from 1928-1929 affected the promotion of integral Yugoslav ideology.